EFFECTIVENESS OF TEACHER PERFORMANCE IN THE CHILDREN'S DEVELOPMENT COGNITIVE ASPECT - Cinantya, Celia; Rafianti, Wahdah Refia; Safitri, Safira Eka (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2024)
The problem in this research is the low level of children's activity and the underdeveloped cognitive development of children in group A. This research approach uses qualitative research with the type of classroom action research, carried out in 4 meetings, the research setting was with the A2 group of Insan Azkia Kindergarten Banjarmasin, totaling 12 children (8 boys and 4 girls). Data collection techniques use observation, documentation, and interviews as well as data analysis using cross tabulation. The aim of this research is to describe teacher activities and analyze children's activities as well as children's cognitive aspects of their abilities. The results of this research show that teacher activities reach the very good category, children's activities reach the very active category, and children's cognitive aspects reach the very well developed category. It is recommended for future researchers that it can be used as information material, as well as for school principals and teachers, it can be used as input to improve children's learning